2010
DOI: 10.1080/08959285.2010.515277
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Distributed Practice on Immediate Posttraining, and Long-Term Performance on a Complex Command-and-Control Simulation Task

Abstract: Using 192 paid participants who trained on a command-and-control microworld simulation, we examined the comparative effectiveness of two distributed practice schedules in enhancing performance at the end of training as well as after an 8-week nonuse period. Longer interstudy intervals (10 hr of practice over 2 weeks) led to higher levels of skill at the end of training and after nonuse than shorter interstudy intervals (10 hr of practice over 1 week). The study begins to address gaps in the skill retention lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…This should be given careful consideration when piloting and designing intervention studies, as this suggests that relying on the parameters of MEP experiments to guide research, as is commonly done, may underestimate the optimum spacing interval required for more complex motor learning tasks, and even more so for cognitive skill learning. For instance, cognitive training studies (without tDCS) have systematically evaluated this phenomenon, finding that once-daily training promoted greater learning and transfer than shorter spacing schedules that involved multiple training sessions per day (Arthur et al 2010;Wang et al 2014). Moreover, it has been demonstrated that the optimal spacing interval increases in correspondence with longer retention intervals.…”
Section: Spacing Of Stimulationmentioning
confidence: 99%
“…This should be given careful consideration when piloting and designing intervention studies, as this suggests that relying on the parameters of MEP experiments to guide research, as is commonly done, may underestimate the optimum spacing interval required for more complex motor learning tasks, and even more so for cognitive skill learning. For instance, cognitive training studies (without tDCS) have systematically evaluated this phenomenon, finding that once-daily training promoted greater learning and transfer than shorter spacing schedules that involved multiple training sessions per day (Arthur et al 2010;Wang et al 2014). Moreover, it has been demonstrated that the optimal spacing interval increases in correspondence with longer retention intervals.…”
Section: Spacing Of Stimulationmentioning
confidence: 99%
“…Other studies examined the acquisition of motor skills (Lee & Genovese, 1988). More recently, researchers have turned to complex skills and knowledge, such as language syntax (Bird, 2010), mathematical concepts (Rohrer & Taylor, 2006), reading (Seabrook et al, 2005), and military command and control (Arthur et al, 2010). In nearly all cases, distributed practice facilitates retention.…”
Section: Applicable To a Variety Of Tasks And Performance Measuresmentioning
confidence: 99%
“…Microworlds have been widely adopted in human-factors research and cognitive systems engineering, considering scenarios such as naval warfare [28], industrial process control [29], air traffic control [30], naturalistic decision-making [27], fire fighting [31], and other complex problem solving scenarios [32,33].…”
Section: Microworld Approachmentioning
confidence: 99%